CSR digitalization: Empowering female MSMEs by Indonesian Telco - Enjang Pera Irawan (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2024)
Many companies have accelerated the implementation of CSR digitalization, especially in helping Indonesia's SME sector, due to the rise of the digital era. This explores the steps taken by telecommunications giants to support the empowerment of female small business owners through digitalization. This research aims to analyze how digitalization can help these women become more capable, access new markets, and ultimately improve their financial independence. The theory of communicative action serves as the guide in exploring this research. A total of 11 informant representing XL Axiata, partners, and SMEs participated in this study through in-depth one-on-one qualitative interviews. The research results indicate that CSR digitalization initiatives can represent the organization's ethical responsibility to support positive social reform in addition to economic contributions. However, inadequate ICT infrastructure needs to be addressed through cross-sector collaboration. Effective messaging, high levels of stakeholder participation, and the demand for two-way communication must collectively address this issue. Cross-sector collaboration can pave the way for a more sustainable and inclusive digital economy in Indonesia).